Penerapan Teknologi “KOPKA” (Kran Otomatis dan Pengukur Kapasitas Air) pada Bak Penampung Air Drip Irrigation untuk Mempermudah Kerja Kelompok Tani Banyu Urip Desa Tanggumong Kecamatan Sampang - Weny Indah Kusumawati; Stephanie Astrid Ayu; Musayyanah, Musayyanah; Yunanto Tri Laksono; Charisma Dimas Affandi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Banyu Urip Farmer Group faces challenges in managing water for agricultural irrigation purposes. One of the main problems is that irrigation in the fields used still uses manual watering techniques, so it takes a long time to do watering. To overcome this problem, the Banyu Urip Farmer Group collaborated with Universitas Dinamika to install an Automatic Faucet and Water Capacity Meter system. This Automatic Faucet and Water Capacity Meter system is an innovation that helps improve irrigation efficiency and water management on farms. This technology provides convenience for farmers in terms of water control, which has a positive impact on resource use efficiency, and supports sustainable agriculture in Tanggumong Village, Sampang District. Community service activities have been completed according to the predetermined schedule. The success of this activity can be measured by the ease felt by Poktan in operating the application to monitor equipment, being able to fill in content on Instagram, and their enthusiasm to take part in the next community service programs.